Keefektifan Teknik Metafora dalam Bingkai Konseling Realitas untuk Meningkatkan Harga Diri Siswa - Diniy Hidayatur Rahman (Universitas Kanjuruhan Malang, 2015)
This study evaluated the effect of metaphor as a reality counseling technique on self-esteem of senior high school students. To achieve that aim, the study applied pretest, middle-test and posttest control group design. Participants in the experimental group (n=5) received metaphor as a technique of reality counseling, whereas participants of the control group (n=5) received reality counseling without metaphor. The analysis of data suggests that: (1) the metaphor is more effective than the reality counseling in improving self-esteem in the middle of intervention; and (2) the metaphor is as effective as the reality counseling in improving self-esteem in the end of intervention.